Space encyclopedia : a tour of our solar system and beyond - Aguilar, David A.; Pulliam, Christine; Daniels, Patricia, 1955- (National Geographic, 2020)
Presents a children's encyclopedia of space featuring full-color artwork and photographs, essays, a tour of the solar system, sidebars and fact boxes, timelines, and stargazing tips.